Studies in clinical enzymology - Mullan, Dermot Patrick (Heinemann Medical, 1969)
Studies in Clinical Enzymology presents a critical review of the nature and diagnostic value of enzymes. It discusses the characteristics of iso-enzymes; the enzymes changes in myocardial infarction, cardiomyopathies, and non-ischemic heart failure; and the characteristics of enzymes studied in African heart disease. Some of the topics covered in the book are the simple enzyme kinetics; classification of enzymes; description of activators and co-enzymes; mechanics of enzyme inhibition; effects of drugs in enzyme reactions; function of the cell membrane; distribution of enzymes; mechanism of en.